EDUTOURISM FOR CHILDREN OF JERUKLEUEUT VILLAGE WITH NATURAL SPACE CHILDREN GARDEN PROGRAM - Lisna Novita; Amalia Azzahra (Ann Publisher, 2024)
Edutourism is an innovative approach combining education and tourism, which can bring about positive changes in children's education in rural areas. This article examines the